Determinants diabetes mellitus of productive age - Rr. Vita nur latif nur latif; sumardiyono sumardiyono; setyo sri rahardjo (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
Background : Based on the 2018 Basic Health Research (Riskesdas) Report by the Ministry of Health, in Indonesia there has been an increase in the prevalence of DM to 10.9%. The International Diabetes Federation (IDF) in 2019 placed Indonesia as the 6th ranked country in the number of DM sufferers which reached 10.3 million. Predictions from the IDF state that there will be an increase in the number of DM patients from 10.7 million in 2019 to 13.7 million in 2030. Lifestyle changes and urbanization seem to be important causes of this problem, and will continue to increase in the coming years. Aim : this study aims to determine the determinants of DM in productive age in Pekalongan Regency, Central Java, Indonesia. Methode: This quantitative study used a cross-sectional design approach on 158 research respondents at three selected area, there are the Tirto I, Kedungwuni I, and Wiradesa district, using a questionnaire, GPAQ instrument, and self-efficacy scale. Results : The results of the logistic regression test on the determinants of productive age DM obtained the equation model Y = -3.949 - 2.040 history of heredity + 1.932 physical activity + 2.345 perceived benefits + 2.985 knowledge dm. Conclusion : So that through this logistic regression test it can be concluded that together interacting variables of physical activity, knowledge, perceived benefits have an effect on the incidence of diabetes mellitus in productive age in Pekalongan Regency. keywords: DM determinants, productive age, GPAQ, self-efficacy scale